2001
DOI: 10.1152/ajpcell.2001.280.6.c1576
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the pump-leak balance for Na+ and K+ in malaria-infected erythrocytes

Abstract: In human erythrocytes infected with the mature form of the malaria parasite Plasmodium falciparum, the cytosolic concentration of Na(+) is increased and that of K(+) is decreased. In this study, the membrane transport changes underlying this perturbation were investigated using a combination of (86)Rb(+), (43)K(+), and (22)Na(+) flux measurements and a semiquantitative hemolysis technique. From >15 h postinvasion, there appeared in the infected erythrocyte membrane new permeation pathways (NPP) that caused a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 40 publications
11
144
0
3
Order By: Relevance
“…There was no difference in amplitude of the inwardly rectifying chloride channel compared with trophozoite-infected cells (Fig. 4D), implying that full activation of the channel is already achieved at an early stage of infection, long before activation of the new permeation pathway (n ϭ 4) (22).…”
Section: Resultsmentioning
confidence: 93%
“…There was no difference in amplitude of the inwardly rectifying chloride channel compared with trophozoite-infected cells (Fig. 4D), implying that full activation of the channel is already achieved at an early stage of infection, long before activation of the new permeation pathway (n ϭ 4) (22).…”
Section: Resultsmentioning
confidence: 93%
“…While the recently described albitiazolium entry via NPP (18) likely explains its specific tropism for IRBC, these pore-like systems do not mediate concentrative processes (44). Albitiazolium accumulation requires intracellular binding sites or active transport in parasite-specific compartments, or a combination of both.…”
Section: Discussionmentioning
confidence: 96%
“…Merckx et al (2009) also report that in order to survive within erythrocytes, parasites alter the permeability of the host plasma membrane, either by upregulating existing transporters, or by creating NPPs. Staines et al (2001) found that Na…”
Section: Discussionmentioning
confidence: 99%